Bonded Labour : Global and Comparative Perspectives (18th-21st Century) - Damir-Geilsdorf, Sabine; Lindner, Ulrike; Müller, Gesine; Tappe, Oliver; Zeuske, Michael (2016)
Parallel to the abolition of Atlantic slavery, new forms of indentured labour stilled global capitalism's need for cheap, disposable labour. The famous 'coolie trade' - mainly Asian labourers transferred to French and British islands in the Indian Ocean, Australia, Indonesia, South Africa, the Caribbean, the Americas, as well as to Portuguese colonies in Africa - was one of the largest migration movements in global history. Indentured contract workers are perhaps the most revealing example of bonded labour in the grey area between the poles of chattel slavery and 'free' wage labour. This interdisciplinary volume addresses historically and regionally specific cases of bonded labour relations from the 18th century to sponsorship systems in the Arab Gulf States today.